Pharmacogenetics testing for poor response to antidepressants: a transnosographic case series - Lorvellec, Marie-Agnès; Sipahimalani, Gilles; Lahutte, Bertrand; Delacour, Hervé; Baldacci, Antoine; Saguin, Emeric (Frontiers in Pharmacology, 2024)
Pharmacogenetics (PGx) holds promise to help optimize the use of psychotropic medications, with CYP2D6 and CYP2C19 emerging as clinically relevant genes in antidepressant treatment. However, there are currently very few studies investigating the genetic variants of CYP2D6 and CYP2C19 in a population of patients experiencing either ineffectiveness or adverse drug reactions (ADRs) to antidepressants in real-world settings, i.e., longitudinally regardless of the treatment indication.In our psychiatry department, PGx testing is now available in clinical practice to help with prescribing antidepressants properly, predicting the right dose and improving treatment outcomes. We present a case series involving 40 patients (82.5% of European origin) who underwent PGx testing due to ineffectiveness or ADRs to antidepressant treatment between June 2020 and April 2022. We describe their demographic, clinical and genetic features and we have assessed the value of PGx testing by consulting the treating psychiatrists.Among the 40 patients, the most common primary diagnoses were major depressive disorder (60.0%) and post-traumatic stress disorder (30.0%). Ineffectiveness alone was reported by 26 patients (65.0%), 1 patient (2.5%) reported only ADRs while 13 (32.5%) reported both ADRs and ineffectiveness. Antidepressant classes represented in this study were SSRIs (45.0%), SNRIs (27.5%), atypical antidepressants (20.0%) and tricyclic antidepressants (17.5%). Only 7 out of 40 patients (17.5%) had normal metabolic activity for CYP2D6 and CYP2C19.We identified 50 CYP2D6/CYP2C19-antidepressant-response pairs, deemed 'actionable' if the CYP phenotypes potentially contributed to the observed response. We found actionability in 11.5% of CYP2D6-antidepressant-response pairs and 33.3% of CYP2C19-antidepressant-response pairs. In our cohort, CYP2D6 and CYP2C19 genotypes were actionable for a total of 22.0% pairs. The PGx algorithm recommendations were followed in 92.7% of cases. According to practitioners, 71.4% of patients showed a considerable decrease (≥ 3/5) of ADRs and 79.5% showed a considerable improvement in efficacy (≥ 3/5).Although the limited sample size invites caution, our findings suggest that patients experiencing ADRs or ineffectiveness to antidepressants exhibit a relatively high prevalence of genetic variants in pharmacogenes known to influence the pharmacokinetics of these medications. The widespread adoption of targeted use of PGx testing in Psychiatry departments could prove beneficial in guiding prescribing decisions.